العزلة الوظيفية وتأثيرها على انجاز الاعمال بإتقان: المسببات والحلول: JOB ISOLATION AND ITS IMPACT ON COMPLETING WORK EFFICIENTLY: CAUSES AND SOLUTIONS - Khalfan, Fahad; Khan, Issa; Muwazir, Mohd Rizal (Online Journal of Islamic Management and Finance (OJIMF), 2024)
In this research paper, the researcher seeks to find out the causes of job isolation and its impact on the proficient completion of work among employees of the State Council and the Shura Council in the Sultanate of Oman, the problem crystallizes in understanding the causes of job isolation and its impact on the completion of work and tasks with perfection. The researcher also seeks to know the extent of the degree of job isolation among the study sample, and the extent of its impact on the completion of work with perfection. The researcher relied on the descriptive analytical approach to analyze the impact of the phenomenon of functional isolation. The quantitative approach was also used, based on the questionnaire, as a tool for collecting primary data. The researcher sought to distribute the questionnaire to the study population, which numbered 171 to obtain the results. The researcher's findings concluded that there were low levels of feeling of lack of power، Also, the results showed, there is a medium level of feeling of functional isolation, and there is also a medium level of feeling of self-estrangement. On the other hand, the results showed that there was an average level of self-confidence, completing work efficiently, and effective social communication. The study also reached a number of recommendations, the most prominent of which are Establish clear specifications and a clear professional job description for each career path within the State Council and the Shura Council and inform employees about it, Establishing clear standards for evaluating institutional performance, which the employee can review, and linked to job specializations, international models can be used to evaluate performance.